Perfusion Assessment Using Intravoxel Incoherent Motion-Based Analysis of Diffusion-Weighted Magnetic Resonance Imaging: Validation Through Phantom Experiments. Issue 8 (August 2016) - Lee, Ju Hee; Cheong, Hyunhee; Lee, Seung Soo; Lee, Chang Kyung; Sung, Yu Sub; Huh, Jae-Wan; Song, Jung-A; Choe, Han
Abstract : Objectives: The aims of this study were to demonstrate the theoretical meaning of intravoxel incoherent motion (IVIM) parameters and to compare the robustness of 2 biexponential fitting methods through magnetic resonance experiments using IVIM phantoms. Materials and Methods: Intravoxel incoherent motion imaging was performed on a 3 T magnetic resonance imaging scanner using 15 b values (0–800 s/mm 2 ) for 4 phantoms with different area fractions of the flowing water compartment (FWC%), at the infusion flow rates of 0, 1, 2, and 3 mL/min. Images were quantitatively analyzed using monoexponential free biexponential, and segmented biexponential fitting models. Results: There were some inconsistent variations in D slow with changing flow rates. The perfusion fraction, f, showed a significant positive correlation with the flow rate for both the free and segmented fitting methods (ρ = 0.838 to 0.969; P < 0.001). The fast diffusion coefficient, D fast, had a significant positive correlation with the flow rate for segmented fitting (ρ = 0.745 to 0.969; P < 0.001), although it showed an inverse correlation with the flow rate for free fitting (ρ = −0.527 to −0.791; P ⩽ 0.017). Significant positive correlations with the FWC% of the phantoms were noted for f ( P = 0.510 for free fitting and P = 0.545 for segmented fitting, P < 0.001). Conclusions: The IVIM model allows for an approximate segmentation of molecular diffusion and perfusion, with a minor contribution of the perfusion effect on D slow . The f and D fast can provide a rough estimation of the flow fraction and flow velocity. Segmented fitting may be a more robust method than free fitting for calculating the IVIM parameters, especially for D fast . Abstract : Supplemental digital content is available in the text.